United States : Report on Observance of Standards and Codes-Fiscal Transparency. (IMF Staff Country Reports; Country Report, 2003)
This paper analyzes the Report on the Observance of Standards and Codes on fiscal transparency for the United States. It assesses fiscal transparency practices in the United States against the requirements of the IMF Code of Good Practices on Fiscal Transparency. It reviews the description of practice, prepared by the IMF staff on the basis of discussions with the United States authorities and their responses to the fiscal transparency questionnaire, and provides a commentary of IMF staff on fiscal transparency in the United States.